Strategi Optimalisasi Pengembangan dan Pemberdayaan Sumber Daya Manusia Menuju Madrasah Berprestasi - Alifia Taufika Rahmah; Fatimatul Baroroh; Rafid Mauludi; Armai Arief; Hasyim Asy'ari (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2023)
Improving the quality of madrasas is often constrained by the low competitiveness of human resources. Even so, several madrasas seem capable of optimizing their resources so that they can become outstanding madrasas. The purpose of this research is to describe how madrasah efforts or strategies to optimize the development and empowerment of their human resources lead to outstanding madrasas. The research was conducted at MTsN 31 Jakarta. The subjects of this study were school administrative staff, teachers, principals and vice principals. The research uses a qualitative approach with data collection techniques namely observation, interviews and documentation. Through three steps of data analysis: data reduction; display data; and conclusion drawing, the results showed that there were five efforts made by madrasas: (1) training for teachers and school administrative staff; (2) optimization of supervision activities; (3) encouraging the active role of teachers in competency development and career development; (4) increasing the competence of madrasah leaders; (5) deliberation culture and building participatory atmosphere. this finding has implications for madrasa managers to pay attention to these five key factors to be implemented if they expect achievement in madrasas.